Human Aging and Longevity Are Characterized by High Levels of Mitokines. (27th June 2018) - Conte, Maria; Ostan, Rita; Fabbri, Cristina; Santoro, Aurelia; Guidarelli, Giulia; Vitale, Giovanni; Mari, Daniela; Sevini, Federica; Capri, Miriam; Sandri, Marco; Monti, Daniela; Franceschi, Claudio; et al.
Abstract: Mitochondrial stress elicits the production of stress response molecules indicated as mitokines, including fibroblast growth factor 21 (FGF21), growth differentiation factor 15 (GDF15), and humanin (HN). Many diseases are characterized by progressive mitochondrial dysfunction with alterations of mitokine secretion. It is still controversial whether healthy aging and extreme longevity are accompanied by an altered production of mitokines. We analyzed FGF21, HN, and GDF15 plasma levels in 693 subjects aged from 21 to 113 years, and the association of these mitokines with parameters of health status. FGF21, HN, and GDF15 resulted increased in old age, with the highest levels found in centenarians. These molecules are associated with worsened parameters (such as handgrip strength, insulin sensitivity, triglycerides), particularly in 70-year-old persons, and their levels are inversely correlated with survival in the oldest subjects. Considering the positive biological effect of these molecules, our results can be interpreted in the framework of the hormetic paradigm as an attempt of the cells/tissues to cope with a stress that can have beneficial or detrimental effects depending on its intensity. Finally, persons with Down Syndrome (characterized by accelerated aging) have higher levels of GDF15 and HN with respect to their siblings, suggesting that these molecules, especially GDF15, could be considered markers of biological age.